Inverted Takotsubo Syndrome With HELLP Syndrome: A Case Report - Gabarre, Paul; Ruiz, Pablo; Chenevier-Gobeaux, Camille; Charpentier, Etienne; Soulat-Dufour, Laurie; Cohen, Ariel; Monnier-Cholley, Laurence; Chemali, Lotfi; François, Hélène; Kerneis, Mathieu; Lefèvre, Guillaume; Boissan, Mathieu (Frontiers in Cardiovascular Medicine, 2022)
Background Takotsubo syndrome is an acute cardiac condition involving sudden, transient apical ballooning of the left ventricle of the heart that may be triggered by emotional stress and some non-cardiac conditions. Its diagnosis is based on clinical presentation, electrocardiogram, cardiac imaging and biomarkers. Case Summary Here, we present a novel and original case report of a patient presenting very soon in the post-partum period with an unusual form of Takotsubo syndrome without clinical symptoms of cardiac disease and accompanied by HELLP syndrome. The overall dynamics of the changes in troponin I, troponin T and NT-proBNP levels after delivery were generally similar, but the amount of troponin I was much greater than that of troponin T and troponin I was already elevated before delivery. NT-proBNP levels peaked around the same time as the troponins and the peak concentration was within the same range as that of troponin I. Discussion Our findings indicate that assaying circulating cardiac biomarkers, especially troponin I and NT-proBNP, may be a useful complement to non-invasive cardiac imaging including transthoracic echocardiography and cardiovascular magnetic resonance imaging, in the diagnosis of Takotsubo syndrome. They illustrate the importance of cardiac biomarkers in assisting diagnosis of this disease.